2007
DOI: 10.1136/ard.2006.065615
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response to adalimumab: relationship to anti-adalimumab antibodies and serum adalimumab concentrations in rheumatoid arthritis

Abstract: Background: A substantial proportion of patients with rheumatoid arthritis (RA) do not respond, or lose initial response, to adalimumab treatment. One explanation for non-response is that patients develop antiadalimumab antibodies. Objectives: To evaluate the incidence of formation of antibody against adalimumab and the association with serum adalimumab concentrations and clinical response. Methods: In a cohort of 121 consecutive patients with RA treated with adalimumab, serum adalimumab concentrations and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
377
4
20

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 501 publications
(424 citation statements)
references
References 15 publications
23
377
4
20
Order By: Relevance
“…The detection of antibodies is dependent on the patient population studied, the timing and frequency of serum sampling, and the sensitivity and specificity of the detection assay used. Thus, the reported incidence can vary greatly between studies of the same biologic agent (3,15,16). In the present study, we employed a sensitive assay to study antibody production both while patients were receiving study medication, as is typically reported for other products, and after a 20-week washout following the last study injection, when golimumab concentrations would likely be low enough to minimize interference with antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of antibodies is dependent on the patient population studied, the timing and frequency of serum sampling, and the sensitivity and specificity of the detection assay used. Thus, the reported incidence can vary greatly between studies of the same biologic agent (3,15,16). In the present study, we employed a sensitive assay to study antibody production both while patients were receiving study medication, as is typically reported for other products, and after a 20-week washout following the last study injection, when golimumab concentrations would likely be low enough to minimize interference with antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of antibodies to TCZ may reduce efficacy and systemic reactions to injections of anti‐TNF inhibitors would occasionally cause lack of efficacy due to the expression of antidrug antibodies 16, 17, 18, 19. In a previous study, we found the anti‐TCZ antibody frequency to be increased in TCZ‐SC patients as compared to TCZ‐IV patients in the double‐blind setting 9.…”
Section: Discussionmentioning
confidence: 82%
“…Inadequate response to tumor necrosis factor ␣ (TNF␣)-blocking therapy in rheumatoid arthritis (RA) may result from the formation of antibodies against these drugs (1). Previous studies have shown that polymorphisms in the promoter region of the gene for interleukin-10 (IL-10), a cytokine with a key role in antibody formation, are associated with the formation of antibodies that inhibit recombinant factor VIII (FVIII) in hemophilia (2) and with the development of autoantibodies against nicotinic acetylcholine receptor (nAChR) in myasthenia gravis (MG) (3).…”
mentioning
confidence: 99%